Kepentingan Pendidikan Humanistik dalam Pengembangan Psikologi - Zainal Badri, Khairul Nizam bin; Andi, Hari Khrisnan (Dinamika Jurnal Ilmiah Pendidikan Dasar, 2020)
This article aims to analyze the importance of humanistic education from a psychological standpoint. Humanistic education can be considered as a form of education that promotes positive psychological development. Through humanistic education, human dignity is elevated as much as human intellect can be, and thinking can be further developed. Humanistic education also enlivens human nature through the realization of one's existence. However, humanistic education must be in line with religion so that students will not be confused by the true meaning of freedom. True human values must be based on religion and not on mere logic